Application of titanium extraction tailings, lightweight non-dismantling building template and preparation method of lightweight non-dismantling building template

By combining titanium-elevated tailslag with other raw materials, low-cost, high-performance lightweight dismantling-free building formwork is prepared, which solves the problems of high cost of traditional formwork and storage of titanium-elevated tailslag, and is suitable for prefabricated construction fields.

CN119797842APending Publication Date: 2025-04-11PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510003152.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing demolition-free building formwork is costly, the equipment needs are strict and the product performance is overwhelming, making it difficult to effectively apply in reinforced concrete buildings. At the same time, the problem of titanium tailslag storage has not been effectively solved.

Method used

Titanium-elevated tailings are used as raw materials, combined with gelling raw materials, lightweight raw materials, fibers and admixtures, and lightweight building formwork is prepared through roll forming-steam maintenance process.

Benefits of technology

It realizes a lightweight, demolition-free building formwork with low cost and moderate performance, reduces energy consumption and early investment costs, effectively utilizes the resources for titanium tailings, and improves the building prefabrication rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797842A_ABST
    Figure CN119797842A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials and metallurgical environmental protection, in particular to application of titanium extraction tailings, a lightweight non-dismantling building template and a preparation method of the lightweight non-dismantling building template. The invention provides an application of titanium extraction tailings in preparation of a lightweight non-dismantling building template. Titanium extraction tailings, a gelling raw material, a light raw material, fibers and an additive are used as main raw materials, and the disassembly-free building template material is prepared through a roll forming-steam curing process. Wherein the titanium extraction tailings can be used as fine aggregate and an active raw material to improve the mechanical property of the material and reduce the material cost; the light raw materials and the fibers can reduce the volume density of the non-dismantling building template and improve the impact resistance of the non-dismantling building template; the selection and optimization of the additives can improve the comprehensive performance of the building non-dismantling formwork, and the building non-dismantling formwork has good economic benefits. All the components can be well matched, and the comprehensive performance of the finally obtained non-dismantling building formwork is excellent. In addition, the selected materials are low in cost, and the utilization rate of solid waste resources is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical fields of building materials and metallurgical environmental protection, and in particular to an application of titanium-extracting tailings, a lightweight, non-disassembly building template and a preparation method thereof. Background Art

[0002] Traditional reinforced concrete formwork is mainly wooden formwork. When the concrete is solidified, the formwork needs to be separated from the building and removed, and can be recycled about 3 times. The use of wooden formwork has the problems of cumbersome construction process, high cost and large wood consumption. The research on non-disassembly formwork is suitable for the development of prefabricated construction industry. On the one hand, it can avoid the problem of multiple disassembly of formwork and reduce labor costs; on the other hand, the use of non-disassembly formwork can further increase the prefabrication rate of the construction industry, meet national policy requirements, and improve the comprehensive performance of buildings. At present, domestic non-disassembly building formwork is in a rapid development stage. Similar products are mostly prepared by semi-dry method, copying method and autoclave curing method. This method has strict equipment requirements, large initial investment, and heavy formwork. If used as reinforced concrete non-disassembly building formwork, it is difficult to load and unload the building, the cost is high, and the product performance is excessive. Therefore, it is very necessary to develop low-cost, moderate-performance lightweight non-disassembly building formwork.

[0003] Titanium-extracting tailings are the product of high-temperature carbonization-low-temperature selective chlorination of titanium-containing blast furnace slag, and contain 3wt% to 5wt% of chloride ions. It is not easy to be directly used as a concrete admixture, resulting in a large amount of titanium-extracting tailings being stored. The resource utilization of titanium-extracting tailings is one of the important conditions for the stable development of the production line of titanium-containing blast furnace slag through high-temperature carbonization-low-temperature selective chlorination. Summary of the invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide an application of titanium extraction tailings, a lightweight non-disassembly building formwork and a preparation method thereof. The non-disassembly building formwork provided by the present invention uses titanium extraction tailings as raw materials and has good economic benefits. At the same time, the comprehensive performance of the non-disassembly building formwork provided by the present invention is better.

[0005] The invention provides an application of titanium-extracted tailings in preparing a lightweight, non-disassembly-required building formwork.

[0006] Preferably, the titanium extraction tailings include:

[0007]

[0008]

[0009] The sum of the amounts of the various components used is 100%.

[0010] The present invention also provides a lightweight, non-disassembly-required building template, which is prepared from raw materials including the following components:

[0011]

[0012] The sum of the amounts of the various components used is 100%.

[0013] Preferably, the cementitious raw material includes at least one of 42.5 silicate cement, 52.5 silicate cement and sulphoaluminate cement;

[0014] In the 42.5 silicate cement, the mass content of SiO2 is 20% to 25%, the mass content of CaO is 45% to 65%, and the mass content of Al2O3 is 5% to 10%;

[0015] In the 52.5 silicate cement, the mass content of SiO2 is 15% to 35%, the mass content of CaO is 30% to 55%, and the mass content of Al2O3 is 10% to 20%;

[0016] In the sulphoaluminate cement, the mass content of SiO2 is 5% to 15%, the mass content of CaO is 40% to 60%, and the mass content of Al2O3 is 15% to 25%.

[0017] Preferably, the lightweight raw material includes at least one of fly ash, silica fume and perlite;

[0018] The mass content of SiO2 in the fly ash is 60% to 80%; the mass content of SiO2 in the silica ash is 80% to 95%; and the particle size of the perlite is 40 to 60 meshes.

[0019] Preferably, the fiber comprises at least one of wood fiber, hemp fiber, bamboo fiber and polypropylene fiber;

[0020] The length of the fiber is 1 to 20 mm.

[0021] Preferably, the water reducer comprises a polycarboxylate water reducer;

[0022] The early strength agent includes at least one of triethanolamine, calcium formate and calcium sulfate;

[0023] The binder includes polyvinyl alcohol.

[0024] The present invention also provides a method for preparing the lightweight non-disassembly building formwork described above, comprising the following steps:

[0025] S1) wet mixing raw materials including titanium extraction tailings, gelling raw materials, lightweight raw materials, fibers, water reducing agent, early strength agent, binder and water to obtain slurry;

[0026] S2) rolling the slurry into a wet blank of a template;

[0027] S3) placing the mold in a steam curing room for curing to obtain a lightweight, non-dismantling building formwork.

[0028] Preferably, in step S1), during the wet mixing process, the mass ratio of water to gelling raw material is 0.4-0.6:1;

[0029] The wet mixing time is 15 to 25 minutes.

[0030] Preferably, in step S2), after obtaining the wet blank of the template, the step further includes: attaching a mesh cloth to the surface of the wet blank;

[0031] The mesh size of the mesh cloth is 3-6 mm, and the weight of a single layer of mesh cloth is 50-80 g / cm 2 ; The number of layers of the mesh cloth is 1 to 3;

[0032] In step S3), the curing time is 3 to 7 days.

[0033] Titanium-extracted tailings have high volcanic ash activity. Therefore, based on the solid waste characteristics and the current application status of building non-disassembly formwork, the present invention provides an application of titanium-extracted tailings for preparing lightweight non-disassembly building formwork. Specifically, the application of the titanium-extracted tailings as a raw material for preparing lightweight non-disassembly building formwork can effectively reduce product costs and is suitable for application in the construction industry in Panxi and surrounding areas.

[0034] The present invention uses titanium-extracting tailings, gelling raw materials, lightweight raw materials, fibers and admixtures as main raw materials, and prepares the non-disassembly building formwork material through a roller forming-steam curing process. Among them, titanium-extracting tailings can be used as fine aggregate and active raw materials to improve the mechanical properties of the material, while reducing the material cost; lightweight raw materials and fibers can reduce the volume density of the non-disassembly building formwork and improve its impact resistance; the selection and optimization of admixtures can improve the comprehensive performance of the non-disassembly building formwork, and has good economic benefits. The various components can cooperate well with each other, and the comprehensive performance of the non-disassembly building formwork finally obtained is better.

[0035] The titanium-extracting tailings utilized in the present invention are unique high-activity tailings produced after high-temperature carbonization and low-temperature selective chlorination of Panzhihua Iron and Steel. The present invention can effectively solidify the chloride ions in the titanium-extracting tailings, and the chloride salts in the titanium-extracting tailings can accelerate the hydration of tricalcium silicate in cement as an early strength agent, thereby improving the early strength of the non-dismantling formwork and increasing the product production cycle rate. The fibers selected in the present invention include bamboo fibers, wood fibers, hemp fibers and polypropylene fibers, which are easy to obtain and suitable for production in different regions. The present invention does not need to adopt semi-dry methods, copying methods and autoclave curing processes, which can effectively reduce energy consumption and reduce initial investment costs. The lightweight raw materials selected in the present invention are low in cost and widely available, and the selected materials are relatively low in cost. The obtained products are more compatible as lightweight non-dismantling formwork for construction projects.

[0036] The present invention innovatively uses titanium extraction tailings as raw materials, and has the characteristics of lower cost, higher solid waste resource utilization, wide fiber selection, simple process, low energy consumption, and high performance adaptability. As a lightweight, non-disassembly-required building template, it can be widely used in the field of prefabricated buildings. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The present invention provides a flow chart for preparing the lightweight, non-disassembly-required building formwork. DETAILED DESCRIPTION

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The present invention provides an application of titanium-extracted tailings for preparing lightweight non-disassembly building formwork. Specifically, the titanium-extracted tailings are used as a raw material for preparing lightweight non-disassembly building formwork.

[0040] In some embodiments of the present invention, the titanium tailings extraction process comprises:

[0041]

[0042]

[0043] The sum of the amounts of the various components used is 100%.

[0044] Specifically, the content of SiO2 in the titanium extraction tailings is 26wt%, 30wt%, and 35wt%.

[0045] The content of Al2O3 in the titanium extraction tailings is 15wt% and 20wt%.

[0046] The content of CaO in the titanium extraction tailings is 20wt%, 28wt% and 30wt%.

[0047] The content of MgO in the titanium extraction tailings is 10wt%, 7wt% and 5wt%.

[0048] The content of Fe2O3 in the titanium extraction tailings is 1.5wt%, 4wt% and 5wt%.

[0049] The content of CaCl2 in the titanium extraction tailings is 1.5wt% and 2.5wt%.

[0050] The content of MgCl2 in the titanium extraction tailings is 1.0wt% and 2wt%.

[0051] The content of MnCl2 in the titanium extraction tailings is 0.5wt% and 1.0wt%.

[0052] The content of K2O in the titanium extraction tailings is 0.5wt% and 1.0wt%.

[0053] The content of TiO2 in the titanium extraction tailings is 9.0wt%, 10wt% and 15wt%.

[0054] The present invention also provides a lightweight non-disassembly building template, which is prepared from raw materials including the following components; specifically, the template wet blank is made from the raw materials including the following components, and is cured; and the template wet blank is made by roll forming;

[0055]

[0056] The sum of the amounts of the various components used is 100%.

[0057] Specifically, the content of the titanium-extracting tailings is 30wt%, 40wt%, 25wt%, 45wt%, or 50wt%.

[0058] The content of the gelling raw material is 50wt%, 20wt%, 55wt%, 25wt% and 35wt%.

[0059] The content of the light raw material is 10wt%, 20wt% and 15wt%.

[0060] The fiber contents are 9.8wt%, 19.5wt%, 9.5wt%, 14wt% and 24.5wt%.

[0061] The content of the water reducing agent is 0.05wt%, 0.1wt% and 0.2wt%.

[0062] The content of the early strength agent is 0.05wt%, 0.1wt%, 0.2wt% and 0.3wt%.

[0063] The content of the binder is 0.1wt%, 0.3wt%, 0.2wt% and 0.5wt%.

[0064] In some embodiments of the present invention, after obtaining the wet blank of the template, the method further comprises: attaching a mesh cloth to the surface of the wet blank and performing curing.

[0065] The titanium extraction tailings are the titanium extraction tailings described above and can pass through a 40-mesh sieve.

[0066] In some embodiments of the present invention, the cementitious raw material is selected from at least one of 42.5 silicate cement, 52.5 silicate cement and sulphoaluminate cement.

[0067] In the 42.5 silicate cement, the mass content of SiO2 is 20% to 25%, such as 22%; the mass content of CaO is 45% to 65%, such as 55%; and the mass content of Al2O3 is 5% to 10%, such as 8%.

[0068] In the 52.5 silicate cement, the mass content of SiO2 is 15% to 35%, such as 25%; the mass content of CaO is 30% to 55%, such as 40%; the mass content of Al2O3 is 10% to 20%, such as 15%.

[0069] In the sulphoaluminate cement, the mass content of SiO2 is 5% to 15%, such as 10%; the mass content of CaO is 40% to 60%, such as 50%; and the mass content of Al2O3 is 15% to 25%, such as 20%.

[0070] In some embodiments of the present invention, the lightweight raw material is selected from at least one of fly ash, silica ash and perlite; specifically, it can be fly ash or silica ash; or fly ash, silica ash and perlite, with a mass ratio of 2:1:1; or fly ash and silica ash, with a mass ratio of 1:1 or 1:2; or perlite and silica ash, with a mass ratio of 1:1. The mass content of SiO2 in the fly ash is 60% to 80%, such as 70%. The mass content of SiO2 in the silica ash is 80% to 95%, such as 85%. The particle size of the perlite is 40 to 60 meshes.

[0071] In some embodiments of the present invention, the fiber is selected from at least one of wood fiber, hemp fiber, bamboo fiber and polypropylene fiber; specifically, it can be wood fiber or polypropylene fiber; or wood fiber, hemp fiber, bamboo fiber and polypropylene fiber, the mass ratio is 5:5:5:4.5; or bamboo fiber and wood fiber, the mass ratio is 5:2; or bamboo fiber, wood fiber and polypropylene fiber, the mass ratio is 2:0.9:2; or wood fiber and polypropylene fiber, the mass ratio is 3:0.9. The length of the fiber is 1 to 20 mm.

[0072] In some embodiments of the present invention, the water reducer is a polycarboxylate water reducer, which is generally commercially available. The early strength agent is selected from at least one of triethanolamine, calcium formate and calcium sulfate. The binder is polyvinyl alcohol.

[0073] The present invention also provides a method for preparing the lightweight non-disassembly building formwork described above, comprising the following steps:

[0074] S1) wet-mixing raw materials including titanium extraction tailings, gelling raw materials, lightweight raw materials, fibers, water reducing agents, early strength agents and binders to obtain slurry;

[0075] S2) rolling the slurry into a wet blank of a template;

[0076] S3) placing the mold in a steam curing room for curing to obtain a lightweight, non-dismantling building formwork.

[0077] Regarding step S1):

[0078] In some embodiments of the present invention, during the wet mixing process, the mass ratio of water to the gelling raw material is 0.4 to 0.6:1; for example, 0.4:1, 0.6:1, 0.5:1, 0.45:1, 0.55:1.

[0079] The wet mixing time is 15 to 25 minutes, such as 20 minutes.

[0080] Regarding step S2):

[0081] The slurry is roll-formed to form a wet blank of the template.

[0082] In some embodiments of the present invention, after obtaining the wet blank of the template, the method further comprises: attaching a mesh cloth to the surface of the wet blank. The mesh size of the mesh cloth is 3 to 6 mm, and the weight of a single layer of the mesh cloth is 50 to 80 g / cm 2 , such as 70g / cm 2 , 50g / cm 2 、60g / cm 2 、80g / cm 2 The number of layers of the mesh cloth is 1 to 3, for example, 2 layers.

[0083] Regarding step S3):

[0084] Place it in a steam curing room for curing to obtain a lightweight, non-dismantling building formwork.

[0085] In some embodiments of the present invention, the curing temperature is 30-40°C, such as 35°C; the humidity is 55%-65%, such as 60%; and the curing time is 3-7d, such as 3d, 5d, 7d, 5d.

[0086] Figure 1 The present invention provides a flow chart for preparing the lightweight, non-disassembly-required building formwork.

[0087] In the present invention, the titanium-extracting tailings are special chlorine-containing tailings produced in the key production line of high-temperature carbonization and low-temperature chlorination of Panzhihua Iron and Steel Co., Ltd., and have multiple functions in the process of preparing lightweight non-dismantling building formwork:

[0088] 1) The titanium tailings contain a large amount of glass phase, which has good potential activity. In an alkaline environment, OH- destroys the glass structure and promotes the dissolution of -Si-O-Si- and -Si-O- bonds. At the same time, Ca in the gelling system 2+It reacts with silicon-oxygen bonds to form CSH gel. CSH has the ability to solidify chloride ions and can effectively reduce the amount of excess chloride ions dissolved. In the field of non-dismantling building formwork, chlorine-containing additives play an early strength role and increase the product production cycle rate. Compared with traditional chlorine-containing additives such as acyl chloride compounds and single chloride salts, the composite chloride salts (calcium chloride and magnesium chloride, etc.) contained in titanium extraction tailings have better effects on non-dismantling building formwork and better costs. The main reason is that the chloride salts in titanium extraction tailings can slowly release and accelerate the hydration of tricalcium silicate in cement, thereby improving the early strength of the non-dismantling building formwork. At the same time, there is no need to purchase other chlorine-containing additives, thereby reducing the cost of non-dismantling building formwork.

[0089] 2) Titanium-extracted tailings can be used as fine aggregate to fill the pores of lightweight non-dismantling building formwork and play a supporting role. The addition of lightweight raw materials can be used as micro-aggregates to fill the internal pores of lightweight non-dismantling building formwork and improve its mechanical properties. On the other hand, it can reduce the volume density of lightweight non-dismantling building formwork. The addition of fibers can effectively increase the internal force of the formwork, provide growth bases for gels and crystals, and improve the impact resistance of lightweight non-dismantling building formwork. The addition of admixtures will improve the water-cement ratio, early strength and bonding ability of the sample, and improve the comprehensive performance of lightweight non-dismantling building formwork.

[0090] Beneficial effects:

[0091] 1) The present invention proposes for the first time to prepare lightweight non-dismantling building formwork from titanium slag, and realizes the high-value utilization of titanium slag, ensuring the stable operation of the high-temperature carbonization-low-temperature selective chlorination production line of titanium-containing blast furnace slag. The effective components such as silicon and calcium in the titanium slag are efficiently utilized, and at the same time, the chloride ions in the titanium slag are solidified inside the lightweight non-dismantling building formwork, realizing the diversified utilization of titanium slag.

[0092] 2) Compared with the traditional formwork preparation process, the lightweight non-disassembly building formwork prepared by the present invention has made innovations in formula and process. The lightweight non-disassembly building formwork is prepared in collaboration with titanium extraction tailings, gelling raw materials and lightweight raw materials, thereby reducing the material cost of the product. In terms of preparation process, the semi-pressing forming and autoclave curing processes (the parameters of the autoclave curing process are the curing temperature ≥160°C and the pressure in the autoclave ≥0.8MPa) are avoided, and the roller forming process is selected to reduce energy consumption and equipment loss, and has higher safety.

[0093] 3) Performance adaptation: The present invention can effectively reduce the volume density of the material by adding lightweight raw materials and fibers, reduce the assembly burden, and is suitable for high-rise building engineering applications.

[0094] 4) High value of tailings and environmental safety. The selection and addition of wood fiber, bamboo fiber and hemp fiber are more in line with the requirements of building safety materials. The addition of a large amount of titanium tailings can reduce its stockpile and protect the local environment. The lightweight non-disassembly building formwork prepared by the present invention can be used in the field of prefabricated buildings, and has opened up a diversified high-value utilization path for titanium tailings.

[0095] In order to further illustrate the present invention, the application of titanium-extracting tailings, the lightweight non-disassembly building formwork and the preparation method thereof provided by the present invention are described in detail below in combination with the embodiments, but it should not be understood as limiting the scope of protection of the present invention.

[0096] Example 1

[0097] 1. Raw material components:

[0098]

[0099]

[0100] The components of the titanium extraction tailings are:

[0101]

[0102] The titanium extraction tailings can pass through a 40-mesh sieve.

[0103] The cementitious raw material is selected from 42.5 silicate cement, the mass content of SiO2 is 22%, the mass content of CaO is 55%, and the mass content of Al2O3 is 8%.

[0104] The light raw material is selected from fly ash; the mass content of SiO2 in the fly ash is 70%.

[0105] The fiber is wood fiber with a length of 1 to 20 mm.

[0106] The water reducer is a polycarboxylate water reducer.

[0107] The early strength agent is selected from triethanolamine.

[0108] The binder is polyvinyl alcohol.

[0109] 2. Preparation of lightweight non-dismantling building formwork:

[0110] 2-1) Wet-mixing the above raw material components; during the wet-mixing process, the mass ratio of water to the gelling raw material is 0.4:1; the wet-mixing time is controlled to be 20 minutes to obtain a slurry;

[0111] 2-2) The slurry is roll-formed into a template wet blank, and two layers of mesh cloth are attached to the surface of the wet blank; the mesh size of the mesh cloth is 3-6 mm, and the weight of a single layer of mesh cloth is 70 g / cm 2;

[0112] 2-3) Place in a steam curing room for curing for 3 days to obtain a lightweight, non-dismantling building formwork.

[0113] According to the test standard of JC / T412.1-2018 "Fiber Cement Slab Part 1: Asbestos-free Fiber Cement Slab", the performance of the obtained lightweight non-disassembly building formwork was tested. It was found that the saturated flexural strength of the lightweight non-disassembly building formwork was 6.3MPa and the volume density was 1.50g / cm 3 , moisture content 12%, impact strength 1.14KJ / m 2 , chlorine fixation efficiency is 52%.

[0114] Example 2

[0115] 1. Raw material components:

[0116]

[0117] The components of the titanium extraction tailings are the same as those in Example 1.

[0118] The titanium extraction tailings can pass through a 40-mesh sieve.

[0119] The cementitious raw material is selected from 52.5 silicate cement, the mass content of SiO2 is 25%, the mass content of CaO is 40%, and the mass content of Al2O3 is 15%.

[0120] The light raw material is selected from fly ash, silica ash and perlite, with a mass ratio of 2:1:1; the mass content of SiO2 in the fly ash is 70%, the mass content of SiO2 in the silica ash is 85%, and the particle size of the perlite is 40-60 meshes.

[0121] The fibers are wood fibers, hemp fibers, bamboo fibers and polypropylene fibers, with a mass ratio of 5:5:5:4.5 and a length of 1 to 20 mm.

[0122] The water reducer is a polycarboxylate water reducer.

[0123] The early strength agent is selected from calcium formate.

[0124] The binder is polyvinyl alcohol.

[0125] 2. Preparation of lightweight non-dismantling building formwork:

[0126] 2-1) Wet-mixing the above raw material components; during the wet-mixing process, the mass ratio of water to the gelling raw material is 0.6:1; the wet-mixing time is controlled to be 20 minutes to obtain a slurry;

[0127] 2-2) rolling the slurry to form a wet blank, and attaching a layer of mesh cloth on the surface of the wet blank;

[0128] 2-3) Place in a steam curing room for curing for 5 days to obtain a lightweight, non-dismantling building formwork.

[0129] According to the test standard of JC / T412.1-2018 "Fiber Cement Slab Part 1: Asbestos-free Fiber Cement Slab", the performance of the obtained lightweight non-disassembly building formwork was tested. It was found that the saturated flexural strength of the lightweight non-disassembly building formwork was 4.7MPa and the volume density was 1.35g / cm 3 , moisture content 18%, impact strength 2.12KJ / m 2 , chlorine fixation efficiency is 47%.

[0130] Example 3

[0131] 1. Raw material components:

[0132]

[0133] The components of the titanium extraction tailings are the same as those in Example 1.

[0134] The titanium extraction tailings can pass through a 40-mesh sieve.

[0135] The gelling raw material is selected from sulphoaluminate cement, the mass content of SiO2 is 10%, the mass content of CaO is 50%, and the mass content of Al2O3 is 20%.

[0136] The light raw material is selected from silica ash; the mass content of SiO2 in the silica ash is 85%.

[0137] The fiber is polypropylene fiber and has a length of 1 to 20 mm.

[0138] The water reducer is a polycarboxylate water reducer.

[0139] The early strength agent is selected from calcium sulfate.

[0140] The binder is polyvinyl alcohol.

[0141] 2. Preparation of lightweight non-dismantling building formwork:

[0142] 2-1) Wet-mixing the above raw material components; during the wet-mixing process, the mass ratio of water to the gelling raw material is 0.5:1; the wet-mixing time is controlled to be 20 minutes to obtain a slurry;

[0143] 2-2) The slurry is roll-formed into a template wet blank, and two layers of mesh cloth are attached to the surface of the wet blank; the mesh size of the mesh cloth is 3-6 mm, and the weight of a single layer of mesh cloth is 50 g / cm 2 ;

[0144] 2-3) Place in a steam curing room for curing for 3 days to obtain a lightweight, non-dismantling building formwork.

[0145] According to the test standard of JC / T412.1-2018 "Fiber Cement Slab Part 1: Asbestos-free Fiber Cement Slab", the performance of the obtained lightweight non-disassembly building formwork was tested. It was found that the saturated flexural strength of the lightweight non-disassembly building formwork was 7.3MPa and the volume density was 1.72g / cm 3 , moisture content 15%, impact strength 2.05KJ / m 2 , chlorine fixation efficiency is 58%.

[0146] Example 4

[0147] 1. Raw material components:

[0148]

[0149] The components of the titanium extraction tailings are the same as those in Example 1.

[0150] The titanium extraction tailings can pass through a 40-mesh sieve.

[0151] The gelling raw material is selected from sulphoaluminate cement, the mass content of SiO2 is 10%, the mass content of CaO is 50%, and the mass content of Al2O3 is 20%.

[0152] The light raw material is selected from fly ash and silica ash, with a mass ratio of 1:2; the mass content of SiO2 in the fly ash is 70%, and the mass content of SiO2 in the silica ash is 85%.

[0153] The fibers are bamboo fibers and wood fibers, with a mass ratio of 5:2 and a length of 1 to 20 mm.

[0154] The water reducer is a polycarboxylate water reducer.

[0155] The early strength agent is selected from triethanolamine, calcium formate and calcium sulfate, and the mass ratio is 1:1:1.

[0156] The binder is polyvinyl alcohol.

[0157] 2. Preparation of lightweight non-dismantling building formwork:

[0158] 2-1) Wet-mixing the above raw material components; during the wet-mixing process, the mass ratio of water to the gelling raw material is 0.45:1; the wet-mixing time is controlled to be 20 minutes to obtain a slurry;

[0159] 2-2) The slurry is roll-formed into a template wet blank, and a layer of mesh cloth is attached to the surface of the wet blank; the mesh size of the mesh cloth is 3-6 mm, and the weight of a single layer of mesh cloth is 60 g / cm 2 ;

[0160] 2-3) Place in a steam curing room for curing for 3 days to obtain a lightweight, non-dismantling building formwork.

[0161] According to the test standard of JC / T412.1-2018 "Fiber Cement Slab Part 1: Asbestos-free Fiber Cement Slab", the performance of the obtained lightweight non-disassembly building formwork was tested. It was found that the saturated flexural strength of the lightweight non-disassembly building formwork was 4.8MPa and the volume density was 1.58g / cm 3 , moisture content 17%, impact strength 1.85KJ / m 2 , chlorine fixation efficiency is 55%.

[0162] Example 5

[0163] 1. Raw material components:

[0164]

[0165] The components of the titanium extraction tailings are the same as those in Example 1.

[0166] The titanium extraction tailings can pass through a 40-mesh sieve.

[0167] The cementitious raw materials are selected from 42.5 silicate cement, 52.5 silicate cement and sulphoaluminate cement, with a mass ratio of 3:2:2; in the 42.5 silicate cement, the mass content of SiO2 is 22%, the mass content of CaO is 55%, and the mass content of Al2O3 is 8%; in the 52.5 silicate cement, the mass content of SiO2 is 25%, the mass content of CaO is 40%, and the mass content of Al2O3 is 15%; in the sulphoaluminate cement, the mass content of SiO2 is 10%, the mass content of CaO is 50%, and the mass content of Al2O3 is 20%.

[0168] The light raw material is selected from fly ash and silica ash, with a mass ratio of 1:1; the mass content of SiO2 in the fly ash is 70%, and the mass content of SiO2 in the silica ash is 85%.

[0169] The fibers are bamboo fibers, wood fibers and polypropylene fibers, with a mass ratio of 2:0.9:2 and a length of 1 to 20 mm.

[0170] The water reducer is a polycarboxylate water reducer.

[0171] The early strength agent is selected from calcium sulfate.

[0172] The binder is polyvinyl alcohol.

[0173] 2. Preparation of lightweight non-dismantling building formwork:

[0174] 2-1) Wet-mixing the above raw material components; during the wet-mixing process, the mass ratio of water to the gelling raw material is 0.45:1; the wet-mixing time is controlled to be 20 minutes to obtain a slurry;

[0175] 2-2) The slurry is roll-formed into a template wet blank, and three layers of mesh cloth are attached to the surface of the wet blank; the mesh size of the mesh cloth is 3-6 mm, and the weight of a single layer of mesh cloth is 80 g / cm 2 ;

[0176] 2-3) Place in a steam curing room for curing for 7 days to obtain a lightweight, non-dismantling building formwork.

[0177] According to the test standard of JC / T412.1-2018 "Fiber Cement Slab Part 1: Asbestos-free Fiber Cement Slab", the performance of the obtained lightweight non-disassembly building formwork was tested. It can be seen that the saturated flexural strength of the lightweight non-disassembly building formwork is 7.0MPa and the volume density is 1.25g / cm 3 , moisture content 23%, impact strength 3.20KJ / m 2 , chlorine fixation efficiency is 63%.

[0178] Example 6

[0179] 1. Raw material components:

[0180]

[0181] The components of the titanium extraction tailings are the same as those in Example 1.

[0182] The titanium extraction tailings can pass through a 40-mesh sieve.

[0183] The cementitious raw material is selected from 42.5 silicate cement, the mass content of SiO2 is 22%, the mass content of CaO is 55%, and the mass content of Al2O3 is 8%.

[0184] The light raw material is selected from pearlite and silica fume, with a mass ratio of 1:1; the mass content of SiO2 in the silica fume is 85%. The particle size of the pearlite is 40-60 meshes.

[0185] The fibers are wood fibers and polypropylene fibers, with a mass ratio of 3:0.9 and a length of 1 to 20 mm.

[0186] The water reducer is a polycarboxylate water reducer.

[0187] The early strength agent is triethanolamine and calcium sulfate, and the mass ratio is 1:1.

[0188] The binder is polyvinyl alcohol.

[0189] 2. Preparation of lightweight non-dismantling building formwork:

[0190] 2-1) Wet-mixing the above raw material components; during the wet-mixing process, the mass ratio of water to the gelling raw material is 0.55:1; the wet-mixing time is controlled to be 20 minutes to obtain a slurry;

[0191] 2-2) The slurry is roll-formed into a template wet blank, and three layers of mesh cloth are attached to the surface of the wet blank; the mesh size of the mesh cloth is 3-6 mm, and the weight of a single layer of mesh cloth is 60 g / cm 2 ;

[0192] 2-3) Place in a steam curing room for curing for 5 days to obtain a lightweight, non-dismantling building formwork.

[0193] According to the test standard of JC / T412.1-2018 "Fiber Cement Slab Part 1: Asbestos-free Fiber Cement Slab", the performance of the obtained lightweight non-dismantling building formwork was tested. It was found that the saturated flexural strength of the lightweight non-dismantling building formwork was 4.3MPa and the volume density was 1.45g / cm 3 , moisture content 19%, impact strength 2.35KJ / m 2 , chlorine fixation efficiency 65%.

[0194] Example 7

[0195] The difference from Example 5 is:

[0196] The components of the titanium extraction tailings are:

[0197]

[0198] The remaining components and steps are the same as those in Example 5; a lightweight, non-disassembly building formwork is obtained.

[0199] According to the test standard of JC / T412.1-2018 "Fiber Cement Slab Part 1: Asbestos-free Fiber Cement Slab", the performance of the obtained lightweight non-disassembly building formwork was tested. It was found that the saturated flexural strength of the lightweight non-disassembly building formwork was 6.8MPa and the volume density was 1.23g / cm 3 , moisture content 24%, impact strength 3.12KJ / m 2 , chlorine fixation efficiency is 62%.

[0200] Example 8

[0201] The difference from Example 5 is:

[0202] The components of the titanium extraction tailings are:

[0203]

[0204] The remaining components and steps are the same as those in Example 5; a lightweight, non-disassembly building formwork is obtained.

[0205] According to the test standard of JC / T412.1-2018 "Fiber Cement Slab Part 1: Asbestos-free Fiber Cement Slab", the performance of the obtained lightweight non-disassembly building formwork was tested. It can be seen that the saturated flexural strength of the lightweight non-disassembly building formwork is 6.5MPa and the volume density is 1.28g / cm 3 , moisture content 28%, impact strength 2.85KJ / m 2 , chlorine fixation efficiency is 59%.

[0206] Comparative Example 1

[0207] The difference from Example 2 is that (the titanium extraction tailings contain a single chloride salt):

[0208] Components for preparing titanium tailings:

[0209]

[0210] The remaining components and steps are the same as those in Example 2; a lightweight, non-disassembly building formwork is obtained.

[0211] According to the test standard of JC / T412.1-2018 "Fiber Cement Slab Part 1: Asbestos-free Fiber Cement Slab", the performance of the obtained lightweight non-disassembly building formwork was tested. It was found that the saturated flexural strength of the lightweight non-disassembly building formwork was 3.9MPa and the volume density was 1.37g / cm 3 , moisture content 21%, impact strength 1.88KJ / m 2 , chlorine fixation efficiency 44%.

[0212] Comparative Example 2

[0213] The difference from Example 2 is that (the titanium extraction tailings contain two kinds of chloride salts):

[0214] Components for preparing titanium tailings:

[0215]

[0216] The remaining components and steps are the same as those in Example 2; a lightweight, non-disassembly building formwork is obtained.

[0217] According to the test standard of JC / T412.1-2018 "Fiber Cement Slab Part 1: Asbestos-free Fiber Cement Slab", the performance of the obtained lightweight non-disassembly building formwork was tested. It was found that the saturated flexural strength of the lightweight non-disassembly building formwork was 4.1MPa and the volume density was 1.35g / cm 3 , moisture content 20%, impact strength 2.08KJ / m 2 , chlorine fixation efficiency 43%.

[0218] Comparative Example 3

[0219] The difference from Example 2 is that (the composite chloride salt in the titanium extraction tailings is the acyl chloride compound 3,5-dimethylbenzoyl chloride):

[0220] Components for preparing titanium tailings:

[0221]

[0222]

[0223] The remaining components and steps are the same as those in Example 2; a lightweight, non-disassembly building formwork is obtained.

[0224] According to the test standard of JC / T412.1-2018 "Fiber Cement Slab Part 1: Asbestos-free Fiber Cement Slab", the performance of the obtained lightweight non-disassembly building formwork was tested. It was found that the saturated flexural strength of the lightweight non-disassembly building formwork was 3.1MPa and the volume density was 1.37g / cm 3 , moisture content 24%, impact strength 1.46KJ / m 2 , chlorine fixation efficiency is 39%.

[0225] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.

Claims

1. An application of titanium-extracted tailings for preparing lightweight, non-dismantling building formwork.

2. The preparation method according to claim 1, characterized in that: The titanium extraction tailings include: The sum of the amounts of the various components used is 100%.

3. A lightweight, non-disassembly building formwork, prepared from raw materials including the following components; The sum of the amounts of the various components used is 100%.

4. The lightweight, non-disassembly-required building formwork according to claim 3 is characterized in that: The cementitious raw material includes at least one of 42.5 silicate cement, 52.5 silicate cement and sulphoaluminate cement; In the 42.5 silicate cement, the mass content of SiO2 is 20% to 25%, the mass content of CaO is 45% to 65%, and the mass content of Al2O3 is 5% to 10%; In the 52.5 silicate cement, the mass content of SiO2 is 15% to 35%, the mass content of CaO is 30% to 55%, and the mass content of Al2O3 is 10% to 20%; In the sulphoaluminate cement, the mass content of SiO2 is 5% to 15%, the mass content of CaO is 40% to 60%, and the mass content of Al2O3 is 15% to 25%.

5. The lightweight, non-disassembly-required building formwork according to claim 3 is characterized in that: The lightweight raw material includes at least one of fly ash, silica fume and perlite; The mass content of SiO2 in the fly ash is 60% to 80%; the mass content of SiO2 in the silica ash is 80% to 95%; and the particle size of the perlite is 40 to 60 meshes.

6. The lightweight, non-disassembly-required building formwork according to claim 3 is characterized in that: The fiber comprises at least one of wood fiber, hemp fiber, bamboo fiber and polypropylene fiber; The length of the fiber is 1 to 20 mm.

7. The lightweight, non-disassembly-required building formwork according to claim 3 is characterized in that: The water reducer includes a polycarboxylate water reducer; The early strength agent includes at least one of triethanolamine, calcium formate and calcium sulfate; The binder includes polyvinyl alcohol.

8. A method for preparing the lightweight non-disassembly building formwork according to any one of claims 3 to 7, comprising the following steps: S1) wet-mixing raw materials including titanium extraction tailings, gelling raw materials, lightweight raw materials, fibers, water reducing agent, early strength agent, binder and water to obtain slurry; S2) rolling the slurry into a wet blank of a template; S3) placing the mold in a steam curing room for curing to obtain a lightweight, non-dismantling building formwork.

9. The preparation method according to claim 8, characterized in that: In step S1), during the wet mixing process, the mass ratio of water to gelling raw material is 0.4-0.6:1; The wet mixing time is 15 to 25 minutes.

10. The preparation method according to claim 8, characterized in that: In step S2), after obtaining the wet blank of the template, the step further includes: attaching a mesh cloth to the surface of the wet blank; The mesh size of the mesh cloth is 3-6 mm, and the weight of a single layer of mesh cloth is 50-80 g / cm 2 ; The number of layers of the mesh cloth is 1 to 3; In step S3), the curing time is 3 to 7 days.

Citation Information

Cited By

  • Preparation and application of hydrated calcium silicate-hydrated calcium aluminosilicate composite hydration product

    CN121913720A